The Forgotten Jesuit of Catholic Modernism : George Tyrrell's Prophetic Theology - Maher, Anthony M. (Project Muse, 2018)
Reception of the theological voice in the Catholic Church is far from laudable. This book highlights the prophetic voice of one priest-theologian, amongst many others, who courageously challenged the hegemonic abuse of power within the church. The former Jesuit George Tyrrell has rightly been described as "a religious genius," "a revolutionary," and yet also a "mystic-prophet" and "a man of prayer and self-sacrifice." In proposing a Catholicism relevant for the time, and in opposition to clericalism, Tyrrell courageously engaged in a battle with the Roman, Jesuit, and English hierarchical establishment. This book illustrates how Tyrrell's theological challenge to those who would take the church out of history was never effectively refuted, either at the time or since, and that the issues Tyrrell raised are still relevant and alive in the church today. In highlighting Tyrrell's liberation of theology from dogmatism, the current work describes why he was vilified by the Roman hierarchy, expelled from the Jesuits, and eventually excommunicated. Tyrrell's Ignatian-inspired, hope-filled theology should not be forgotten, not least because it sheds further light on another courageous and prophetic Jesuit, Pope Francis. In revisiting Tyrrell's Ignatian theology, this book celebrates the promise that Vatican II presented to the future church, namely, a universal call to holiness that is currently embraced by Pope Francis.